EFEKTIVITAS PEMBELAJARAN DIKJASORKES TIDAK DIPENGARUHI LATAR BELAKANG GURU PEMULA - BUDI PRAKOSO, BAYU (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Teacher is an educator who its role with is to implement the teaching profession should be able to appear as someone who is professional, so not just anyone can carry the profession. It requires professional education to be able to carry a such profession for quality learning. Quality of learning showed by the effectiveness of learning that can be observed from the preparation, implementation of learning by teachers and students learning activities use traditional instruments physical education classroom observations by three observers. It can also be revealed from the results, the volition, methods, and cooperation from the students opinions using questionnaires formative class evaluatian (FCE). In fact the lesson physical education still not run professionally, the proof that it is carried out by teachers from various educational backgrounds. This study aims to find the real information about the comparing of effectiveness in learning and the great differences in terms of the background of the novice teacher. This research is a non-experimental, comparison with quantitative descriptive approach. Sebjek research program is 18 Penjaskesrek students study of S-1 and 25 students S-1 Penkepor field experience program II, which acts as novice teachers in Unesa partner schools is as many as 13 senior high school and vocational schools throughout the city of Surabaya. From the research results can be concluded that there was no significant difference in the effectiveness of the learning value in terms of physical education background novice teachers as evidenced by the results count x2 count < x2table of the two instruments used were from the data FCE amounted to 0,0588 < 3,841 and from the observation for 1,044 < 3,841. The average number of both instruments showed a difference of 0,38% with FCE instrument and by 2,11% with observation instruments. Keywords: background novice teachers, effectiveness of learning physical education.